Relevansi Transformational Leadership Di Lembaga Pendidikan Kristen - Maria Titik Windarwati; Junio Richson Sirait; Hestyn Natal Istinatun; Tamba Parulian; Emeliana Emeliana (Jurnal Pendidikan Agama Kristen (JUPAK), 2021)
Transformational leadership is a leadership model that is still relevant to use today. All Christian educational institutions require this pattern to develop quality in every implementation of the civitas academical. This paper aims to examine the relevance of transformation leadership patterns in Christian educational institutions through literature studies. The method in this research uses literature studies with descriptive analysis techniques. Through this study concluded that transformational leadership patterns are very relevant to be applied. Through this study, concluded that transformational leadership is very relevant to implemented in educational institutions. Transformational leadership has a role important in the achievement of the quality of education in Christian educational institutions.